2015
DOI: 10.3892/or.2015.4442
|View full text |Cite
|
Sign up to set email alerts
|

Cul1 promotes melanoma cell proliferation by promoting DEPTOR degradation and enhancing cap-dependent translation

Abstract: Cullin1 (Cul1) serves as a rigid scaffold in the SCF (Skp1/Cullin/Rbx1/F-box protein) E3 ubiquitin ligase complex and has been found to be overexpressed in melanoma and to enhance melanoma cell proliferation by promoting G1-S phase transition. However, the underlying mechanisms involved in the regulation of melanoma cell proliferation by Cul1 remain poorly understood. In the present study, we found that Cul1 promoted mTORC1 activity and cap-dependent translation by enhancing the ubiquitination and degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…DEPTOR is an mTORC1 inhibitor [30, 31], which is closely related to cell proliferation, inflammation, obesity, and cancer [32, 33] and directly connected with cardiovascular disease [34, 35]. One study reported that DEPTOR regulates vascular EC activation and contributes to proinflammatory and angiogenic responses in vitro [18].…”
Section: Discussionmentioning
confidence: 99%
“…DEPTOR is an mTORC1 inhibitor [30, 31], which is closely related to cell proliferation, inflammation, obesity, and cancer [32, 33] and directly connected with cardiovascular disease [34, 35]. One study reported that DEPTOR regulates vascular EC activation and contributes to proinflammatory and angiogenic responses in vitro [18].…”
Section: Discussionmentioning
confidence: 99%
“…DEPTOR is an inhibitor of both mTORC1 and mTORC2. mTOR activation can phosphorylate DEPTOR and promote its recognition by SCF β-TrCP ubiquitin ligase, targeting DEPTOR for polyubiquitination and proteolytic degradation [ 51 , 52 ]. In tumors with isocitrate dehydrogenase1/2 (IDH1/2) mutations, oncometabolite 2-hydroxyglutarate indirectly promotes DEPTOR polyubiquitination by SCF β-TrCP , thus activating mTOR [ 51 ].…”
Section: Ubiquitination and Metabolic Signaling Pathwaysmentioning
confidence: 99%
“…Consistent with these findings, MLN4924 indeed further inactivated mTORC1 and downregulated NF-κB in HCC cells compared to sorafenib alone. This was mediated by the increase in Deptor and IκBɑ, known substrates of SCF-βTrCP, as demonstrated in melanoma and HCC cancer cell lines (47,48). However, we did not observe an increase in Noxa, a known substrate of CRL5, in the MLN4924 only treatment group in HCC cells.…”
Section: Discussionmentioning
confidence: 83%